Validity and reliability of innovative behaviors of nurses and midwives scale: A scale development study (Annals of Medical Research, 2023)
Aim: This research was carried out to develop a measurement instrument to determine the innovative behaviors of nurses and midwives.Materials and Methods: This study, which is of a methodological nature, was applied with 216 nurses and midwives between 01.06.2021-31.09.2021. The item pool of the scale was created by the researchers with the literature as twenty-three items in a five-point Likert type and submitted to the opinions of twelve specialists.Results: The three-factor scale structure designed by making explanatory and confirmatory factor analysis was confirmed with the validity and reliability. According to the analysis results; the scale consisted of three sub-dimensions (managerial and personal; physical and occupational; organizational and environmental) and 15 items. It was founded that the content validity index of the scale items was 0.468-0.851; factor loads were 0.510-0.871; item-total score correlations were 0.467-0.768, and the Cronbach's alpha reliability coefficient of the sub- dimensions ranged between 0.703-0.876 and it was 0.912 for the whole scale.Conclusion: As a result of the validity and reliability analyzes of the Attitude Scale towards Innovative Behaviors of Nurses and Midwives, it was founded that it can be used as a valid and reliable scale.
Keywords: Innovative behaviors; Reliability; Scale; Midwife; Validity